Virtual Build to order environment: - Predicting inventory behaviour in an open pipeline - Agarwal, Pranav (2007)
In the following thesis an attempt has been made to predict inventory behaviour in a Virtual Build to Order Environment (VBTO). Simulations runs have been undertaken based on the model developed under the FULSIM project to analyze specific stock related metrics originating in a production system. It focuses on a comparative evaluation of the VBTO and the conventional system by changing three-core simulation run parameters i.e. Product Variants Number, Batch Size and Feedback Process. Data obtained from the run has been analyzed using the spreadsheet application Microsoft Excel. Further study focuses on co-relating the traits observed with basic inventory theory like the Newsboy Model, identify pitfalls, and suggest areas for further research.